Concordance of antibiotic prescribing with the American Dental Association acute oral infection guidelines within Veterans' Affairs (VA) dentistry. (2nd December 2021) - Carlsen, Daniel B.; Durkin, Michael J.; Gibson, Gretchen; Jurasic, M. Marianne; Patel, Ursula; Poggensee, Linda; Fitzpatrick, Margaret A.; Echevarria, Kelly; McGregor, Jessina; Evans, Charlesnika T.; Suda, Katie J.
Abstract: Objective: United States dentists prescribe 10% of all outpatient antibiotics. Assessing appropriateness of antibiotic prescribing has been challenging due to a lack of guidelines for oral infections. In 2019, the American Dental Association (ADA) published clinical practice guidelines (CPG) on the management of acute oral infections. Our objective was to describe baseline national antibiotic prescribing for acute oral infections prior to the release of the ADA CPG and to identify patient-level variables associated with an antibiotic prescription. Design: Cross-sectional analysis. Methods: We performed an analysis of national VA data from January 1, 2017, to December 31, 2017. We identified cases of acute oral infections using International Classification of Disease, Tenth Revision, Clinical Modification (ICD-10-CM) codes. Antibiotics prescribed by a dentist within ±7 days of a visit were included. Multivariable logistic regression identified patient-level variables associated with an antibiotic prescription. Results: Of the 470, 039 VA dental visits with oral infections coded, 12% of patient visits with irreversible pulpitis, 17% with apical periodontitis, and 28% with acute apical abscess received antibiotics. Although the median days' supply was 7, prolonged use of antibiotics was frequent (≥8 days, 42%–49%). Patients with high-risk cardiac conditions, prosthetic joints, and endodontic, implant, and oral and maxillofacial surgery dental procedures were more likely to receive antibiotics. Conclusions: Most treatments of irreversible pulpitis and apical periodontitis cases were concordant with new ADA guidelines. However, in cases where antibiotics were prescribed, prolonged antibiotic courses >7 days were frequent. These findings demonstrate opportunities for the new ADA guidelines to standardize and improve dental prescribing practices.